2019
DOI: 10.3892/etm.2019.8206
|View full text |Cite
|
Sign up to set email alerts
|

Changes of cardiac troponin I and hypersensitive C‑reactive protein prior to and after treatment for evaluating the early therapeutic efficacy of acute myocardial infarction treatment

Abstract: The present study aimed to evaluate the utility of the extent of change (C) and change rate (Cr) of cardiac troponin I (cTnI) and hypersensitive C-reactive protein (hs-CRP) prior to and after treatment in evaluating the early therapeutic efficacy of acute myocardial infarction (AMI) treatment. A total of 145 patients with AMI who received regular MI treatment were enrolled in the present study. Patients were divided into the effective group and the ineffective group based on the early therapeutic efficacy. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
(24 reference statements)
1
0
0
Order By: Relevance
“…The same result was observed by (Seyedian et al, 2016) study who reported that there was no significant difference between SA and HC groups. While in both UA and MI patients, the HsCRP marker could be reported very good indicators for patient's diagnosis, these results agree with (Seyedian et al, 2016) (23) study regarding to UA and agree with (Wang et al, 2020) study (24) which stated that the HsCRP has an important clinical value in the MI diagnosis. Also the present study observed that the HsCRP marker is always significant in the diagnosis between all the groups' combinations, as pointed by the many studies such as (23) , (25) and (24) studies.…”
Section: Discussionsupporting
confidence: 85%
“…The same result was observed by (Seyedian et al, 2016) study who reported that there was no significant difference between SA and HC groups. While in both UA and MI patients, the HsCRP marker could be reported very good indicators for patient's diagnosis, these results agree with (Seyedian et al, 2016) (23) study regarding to UA and agree with (Wang et al, 2020) study (24) which stated that the HsCRP has an important clinical value in the MI diagnosis. Also the present study observed that the HsCRP marker is always significant in the diagnosis between all the groups' combinations, as pointed by the many studies such as (23) , (25) and (24) studies.…”
Section: Discussionsupporting
confidence: 85%